Analysis of the Ministry of Religion's Formulation and Policy Regarding the Independence of Islamic Boarding Schools - Imdad, Fuad Imdadur; aliaddin, Alfian; Miftah, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2024)
Policies are intended to be solutions and answers to various problems experienced by society. Analysis of policy formulation is intended to be able to find out about the formulation process and various other stages in the preparation of a policy as well as who the actors are who took part in the formulation of the policy. The Islamic boarding school independence policy initiated by the Ministry of Religion has a good idea as an effort to increase human resources that are independent from an economic perspective who can then continue the role of da'wah and community development among Islamic boarding schools and the wider community. The problem faced is the uneven implementation of Islamic boarding school independence policies throughout Indonesia. Lack of knowledge regarding the ideas and policies themselves is also another problem faced, therefore researchers aim to conduct studies to analyze the formulation and process of developing Islamic boarding school independence policies. The method used in this research is a literature study based on the theory of policy formulation initiated by Dunn. The results of this research show that the formulation and process of formulating policies is in accordance with Dunn's theory. Apart from that, it was also found that the results need to be further improved regarding the distribution of Islamic boarding school independence policies because this policy has quite an important urgency in improving human resources in Islamic boarding schools and is one of 7 programs. work that is a priority for the Ministry of Religion.